The powdery mildew fungus Podosphaera fusca (synonym Podosphaera xanthii), a constant threat to cucurbits - Pérez-García, A.; Romero, D.; Fernández-Ortuño, D.; Lopez-Ruiz, Fran; de Vicente, A.; Torés, J. (Wiley-Blackwell Publishing Ltd., 2009)
Numerous vegetable crops are susceptible to powdery mildew, but cucurbits are arguably the group most severely affected. Podosphaera fusca (synonym Podosphaera xanthii) is the main causal agent of cucurbit powdery mildew and one of the most important limiting factors for cucurbit production worldwide. Although great efforts have been invested in disease control, by contrast, many basic aspects of the biology of P. fusca remain unknown.